The rise and fall of war crimes trials : from Charles I to Bush II - Smith, Charles Anthony (Cambridge University Press, 2012)
"This book is the first comprehensive analysis of the politics of war crimes trials. It provides a systematic and theoretically rigorous examination of whether these trials are used as tools for political consolidation or whether justice is their primary purpose. The consideration of cases begins with the trial of Charles I of England and goes through the presidency of George W. Bush, including the trials of Saddam Hussein and those arising from the War on Terror. The book concludes that political consolidation is the primary concern of these trials - a point that runs contrary to the popular perception of the trials and their stated justification. Through the consideration of war crimes trials, this book makes a contribution to our understanding of power and conflict resolution and illuminates the developmental path of war crimes tribunals"--Provided by publisher.